The Strength of Mini Shell Structure Made from Ultra High Performance Polypropylene Fiber Reinforced Concrete. (2017) - Hardjasaputra, Harianto; Widjajakusuma, Jack; Hoo, Darmanto; Dewobroto, Wiryanto
Abstract: Since 2010 the Authors have been developing ultra high performance concrete (UHPC) using the local Indonesian materials. Our UHPC consists of Ordinary Portland Cement SNI Type 1, quartz sand, marble powder, micro silica, and superplasticizer. Our concrete mix design is able to achieve compressive strength of 130 MPa – 140 MPa in average. From our experiences, the ductility and tensile strength of UHPC can be increased by adding 1% - 2% volume of polypropylene fiber in the concrete mixing, which is designated as ultra high performance polypropylene fiber reinforced concrete (UHPPFRC). This study provides the experimental results of a shells made of UHPPFRC. The shells are intended for using in the boat applications. The 5 mm thickness of UHPPFRC sheet is used as the skin of body boat by attaching them to the surface of Expanded Polystyrene (EPS). The 50 specimens consist of mini shells with 25 cm span and 3-5 mm thickness, constructed by attaching thin sheet of UHPPFRC to the surface of EPS. All the UHPPFRC mini shells will be tested under static loading test. The strength, deformation and cracks growth of UHPPFRC mini shells will be studied in correlation with the variation of shell height and contents of the polypropylene fiber.